Space antenna handbook - Imbriale, W. A. (William A.); Gao, Steven; Boccia, Luigi (Hoboken : John Wiley & Sons, 2012)
This book addresses a broad range of topics on antennas for space applications. First, it introduces the fundamental methodologies of space antenna design, modelling and analysis as well as the state-of-the-art and anticipated future technological developments. Each of the topics discussed are specialized and contextualized to the space sector. Furthermore, case studies are also provided to demonstrate the design and implementation of antennas in actual applications. Second, the authors present a detailed review of antenna designs for some popular applications such as satellite communications.
3.13 Rx Front-End Block3.13.1 Noise Figure and Noise Temperature; 3.14 Received Power in the Communications System's RF Link; 3.14.1 The Angular Dependencies of the Uplink and Downlink; 3.15 Additional Losses in the Satellite and Antenna; 3.15.1 Additional Losses due to Propagation Effects and the Atmosphere; 3.15.2 Ionospheric Effects -- Scintillation and Polarization Rotation; 3.16 Thermal Noise and the Antenna Noise Temperature; 3.16.1 The Interface between the Antenna and the Communications System; 3.16.2 The Uplink Signal to Noise; 3.17 The SNR Equation and Minimum Detectable Signal.
3.18 Power Flux Density, Saturation Flux Density and Dynamic Range.
Includes bibliographical references and index.
Print version record.
Keywords: Antennas (Electronics); Space vehicles -- Radio antennas; Artificial satellites in telecommunication; Engineering; Electrical engineering; TECHNOLOGY & ENGINEERING -- Aeronautics & Astronautics; Antennas (Electronics); Artificial satellites in telecommunication; Space vehicles -- Radio antennas; Electronic books